Developing High School Telegram-Based Listening and Speaking Learning Materials. - Rais, Sulfa; Alberth, Alberth; Miliha, La (Journal of Teaching of English, 2021)
This study was aimed to develop a Telegram-based Listening and Speaking learning materials for high school students in form of a chatbot. This study was used Educational Research and Development model. The subjects of the study were the X Accountant 2 students of Sekolah Menengah Kejuruan Negeri 1 Kendari. The procedure was adapted from ADDIE model proposed by Taylor (2004) which consist of analyzing the studentsâ€™ needs, designing the media flowchart, developing the media, evaluating the media, and finalizing the media. The instruments used to collect the data were needs analysis questionnaire and expert judgment questionnaire. This study developed a Telegram Bot for Listening and Speaking materials which was based in the teacher module given by the school. Based on the research findings from the expert judgment, the interactive multimedia is appropriate for students since the means score for content and media aspects were above 3,4 which were categorized as â€œGoodâ€.